Accuracy of a new fast-setting polyether impression material - Zenthöfer, Andreas; Rues, Stefan; Rammelsberg, Peter; Stober, Thomas (The international journal of prosthodontics, 2020)
Purpose: To evaluate the dimensional accuracy of impressions made using a new fast-setting polyether material. Materials and Methods: A metallic reference model with two crown preparations, one inlay - preparation, and three stainless steel precision balls was digitized to create a digital reference model. Sixteen - one-step impressions were made for each of the four study groups, differing in impression material (regular-setting - polyether [RSP] vs fast-setting polyether [FSP]) and technique (monophase vs dualphase), for a total of - 64 specimens. Plaster casts fabricated from these impressions were digitized using 3D scans. Global accuracy - was studied by evaluating distance and angle deviations between the replica and the reference model. Local - accuracy was described in terms of trueness and precision of the aligned individual abutment tooth surfaces. - Results: For all impression materials and techniques, the local accuracy at the abutment tooth level was - excellent. For surfaces prepared for crowns, mean trueness was < 10 μm, and mean precision < 12 μm. Inlay - surfaces were associated with higher inaccuracies (mean trueness < 21 μm and mean precision < 37 μm). - The greatest global inaccuracies were generally measured for the cross-arch span, with mean distance - changes between -55 μm and -94 μm. For all aspects of studied accuracy, impressions with FSP were at least - comparable to those fabricated with RSP. Conclusion: Within the limitations of this study, all tested polyether - materials would allow for clinically acceptable impression making. The new fast-setting material could be an - alternative to regular-setting polyether materials, especially for single crowns and small fixed partial dentures.